2018
DOI: 10.3389/fmicb.2018.01201
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure and Associations During a Marine Dinoflagellate Bloom

Abstract: Interactions between microorganisms and algae during bloom events significantly impacts their physiology, alters ambient chemistry, and shapes ecosystem diversity. The potential role these interactions have in bloom development and decline are also of particular interest given the ecosystem impacts of algal blooms. We hypothesized that microbial community structure and succession is linked to specific bloom stages, and reflects complex interactions among taxa comprising the phycosphere environment. This invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 125 publications
10
75
0
Order By: Relevance
“…However, when the HAB enters the postbloom stage, a different picture is apparent, i.e., stochastic processes dominate in this period. This may be due to the disturbance (algal bloom event), which resulted in competition based on limited nutrients or space (45). This is further supported by literature demonstrating that competition contributed to the random process of attached bacterial distribution (46).…”
Section: Discussionsupporting
confidence: 54%
“…However, when the HAB enters the postbloom stage, a different picture is apparent, i.e., stochastic processes dominate in this period. This may be due to the disturbance (algal bloom event), which resulted in competition based on limited nutrients or space (45). This is further supported by literature demonstrating that competition contributed to the random process of attached bacterial distribution (46).…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported that associations with Rhizobiales bacteria might play a crucial role in the fitness of Alexandrium strains, as species of the order Rhizobiales have been frequently reported during the blooms of Alexandrium spp. [43–45]. In addition, bacteria from this order have been found in the benthic assemblage of a coral reef ecosystem [46].…”
Section: Discussionmentioning
confidence: 99%
“…This was reflected in the Simpson index as well as the indices for September 2017 being lower than those of the August 2016 or March 2017 samples. Similarly, Zhou et al (2018) demonstrated that the Simpson Indices for bacteria increased after the onset of an algal bloom (Brackish peat, September 2017) whereas the Shannon indices was at the lowest (Brackish peat, March 2017) (when assuming that the region in which phytoplankton blooms occur is the brackish peat region). Overall, there was greater diversity (based on Shannon Indices) in the dry season (August 2016) than the wet seasons (March and September 2017) whereas there were greater OTUs in the wet season (Observed index).…”
Section: Diversity and Shifts In Bacterial Communities Along The Rajamentioning
confidence: 91%